Unexpected Cardiovascular Oscillations at 0.1 Hz During Slow Speech Guided Breathing (OM Chanting) at 0.05 Hz - Hotho, Gerard; von Bonin, Dietrich; Krüerke, Daniel; Wolf, Ursula; Cysarz, Dirk (Frontiers in Physiology, 2022)
Slow breathing at 0.1 Hz (i.e. 6 cycles per minute, cpm) leads to strong cardiovascular oscillations. However, the impact of breathing below 6 cpm is rarely addressed. We investigated the influence of OM chanting, an ancient Indian mantra, with approx. 3 respiratory cpm (0.05 Hz) on the synchronisation of heart rate (RR), respiration (RESP) and systolic blood pressure (SBP). Nine healthy, trained speech practitioners chanted three sequences of five subsequent OM with 2 minutes pauses in between. Each single OM chanting consisted of taking a deep breath and a long ‘OM’ during expiration and lasted approx. 20 s. ECG, respiration and blood pressure were recorded continuously, of which the RR tachogram, RESP and SBP were derived. Synchronisation between the signals was computed using the phase difference between two signals. During OM chanting synchronisation among the oscillations of RR, SBP and RESP was significantly increased compared to rest. Furthermore, OM chanting at breathing frequencies between 0.046 and 0.057 Hz resulted in 0.1 Hz oscillations in RR and SBP. In conclusion, OM chanting strongly synchronized cardiorespiratory and blood pressure oscillations. Unexpected oscillations at 0.1 Hz in SBP and RR appear at breathing frequencies of approx. 0.05 Hz. Such frequency doubling may originate from an interaction of breathing frequency with endogenous Mayer waves.